The pseudodichotomous Dasya sylviae sp. nov. (Delesseriaceae, Ceramiales) from 60–90 m mesophotic reefs off Bermuda - Schneider, Craig W.; Cassidy, Margaret M.; Saunders, Gary W. (European Journal of Taxonomy, 2021)
The red alga Dasya sylviae C.W.Schneid., M.M.Cassidy & G.W.Saunders sp. nov. is described from mesophotic depths of 60–90 m off Bermuda. Genetic sequences (COI-5P, rbcL) and morphological characteristics show that this species is distinct from other known pseudodichotomous species of Dasya. Of ten current species in the genus reported from Bermuda, only three, D. collinsiana M.Howe, D. cryptica C.W.Schneid., Quach & C.E.Lane and D. punicea (Zanardini) Menegh., share the overall pattern of pseudodichotomous branching in their axes; however, key morphological features easily distinguish them from D. sylviae sp. nov. The species most similar in habit to D. sylviae sp. nov. is D. crouaniana J.Agardh (type locality West Indies), but it bears shorter pseudolateral branches, and broader and longer tetrasporangial stichidia than the new species. Unique among the species of Dasya, D. sylviae sp. nov. lacks post-sporangial cover cells in tetrasporangial stichidia.